Agrobacterium tumefaciens - Winans, Stephen (Henry Stewart Talks, 2008)
Agrobacterium and tumor inducing plasmid, T-DNA transfer, Using Agrobacterium to create "transgenic" plants, VirA and VirG, Two component system, Quorum sensing, LuxR-LuxI-like regulatory system composed of TraR and TraI, Acylhomoserine lactones (AHLs), The crystal structure of TraR, TraR and expression of target promoters